Given: (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) Use a calculator to evaluate each of the following: (a) \( \cos (A-B) \) (b) \( \cos A-\cos B \) (c) \( \cos A \cdot \cos B+\sin A \cdot \sin B \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
Let's evaluate each of the cases step by step! We'll use the fact that the cosine of the difference of two angles can be calculated using the formula \( \cos(A - B) = \cos A \cos B + \sin A \sin B \). ### Case (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) 1. **(a) \( \cos (A - B) = \cos(60^{\circ} - 30^{\circ}) = \cos(30^{\circ}) \)** - This yields \( \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \approx 0.866 \) 2. **(b) \( \cos A - \cos B = \cos(60^{\circ}) - \cos(30^{\circ}) \)** - Calculation gives \( \frac{1}{2} - \frac{\sqrt{3}}{2} \approx -0.366 \) 3. **(c) \( \cos A \cdot \cos B + \sin A \cdot \sin B \)** - Results in \( \cos(60^{\circ}) \cdot \cos(30^{\circ}) + \sin(60^{\circ}) \cdot \sin(30^{\circ}) \) - Which calculates to \( \frac{1}{2} \cdot \frac{\sqrt{3}}{2} + \frac{\sqrt{3}}{2} \cdot \frac{1}{2} = \frac{\sqrt{3}}{4} + \frac{\sqrt{3}}{4} = \frac{\sqrt{3}}{2} \approx 0.866 \) ### Case (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) 1. **(a) \( \cos (A - B) = \cos(110^{\circ} - 50^{\circ}) = \cos(60^{\circ}) \)** - This yields \( \cos(60^{\circ}) = \frac{1}{2} \) 2. **(b) \( \cos A - \cos B = \cos(110^{\circ}) - \cos(50^{\circ}) \)** - Calculation gives approximately \( -0.342 - 0.643 \approx -0.985 \) 3. **(c) \( \cos A \cdot \cos B + \sin A \cdot \sin B \)** - Results in \( \cos(110^{\circ}) \cdot \cos(50^{\circ}) + \sin(110^{\circ}) \cdot \sin(50^{\circ}) \) - This will also give \( \frac{1}{2} \) ### Case (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) 1. **(a) \( \cos (A - B) = \cos(225^{\circ} - 135^{\circ}) = \cos(90^{\circ}) \)** - This yields \( \cos(90^{\circ}) = 0 \) 2. **(b) \( \cos A - \cos B = \cos(225^{\circ}) - \cos(135^{\circ}) \)** - Calculation gives \( -\frac{\sqrt{2}}{2} - (-\frac{\sqrt{2}}{2}) = 0 \) 3. **(c) \( \cos A \cdot \cos B + \sin A \cdot \sin B \)** - Results in \( (-\frac{\sqrt{2}}{2}) \cdot (-\frac{\sqrt{2}}{2}) + \sin(225^{\circ}) \cdot \sin(135^{\circ}) \) - This ultimately adds to \( 1 \) In conclusion, here are the results for each case: - Case (i) results: (0.866, -0.366, 0.866) - Case (ii) results: (0.5, -0.985, 0.5) - Case (iii) results: (0, 0, 1)